Effects of additive corticosteroid therapy on 90-day survival in patients with community-onset pneumonia. Issue 4 (April 2022) - Tachiwada, Takashi; Noguchi, Shingo; Muramatsu, Keiji; Akata, Kentaro; Yamasaki, Kei; Kido, Takashi; Asakawa, Takeshi; Fujino, Yoshihisa; Fushimi, Kiyohide; Matsuda, Shinya; Mukae, Hiroshi; Yatera, Kazuhiro
Abstract: Introduction: Systemic corticosteroid therapy is occasionally used as an additive therapy, especially for patients with severe pneumonia. However, its recommendation for use in patients with pneumonia varies worldwide, and its efficacy is unclear. Methods: Adult Japanese patients hospitalized with community-onset pneumonia between January and December 2012 were analyzed using the Diagnostic Procedure Combination database. The patients were classified into mild-to-moderate and severe groups using the A-DROP (age, dehydration, respiration, orientation, and blood pressure) system. The 90-day survival rate was evaluated between the presence or absence of corticosteroid treatment using the Kaplan-Meier method in the overall, mild-to-moderate and severe groups, respectively. The patients' clinical characteristics were adjusted between the two groups using the inverse probability of treatment weighting method. Results: Among 123, 811, 110, 534 patients were classified as mild-to-moderate grade (corticosteroid group: 8, 465, non-corticosteroid group: 102, 069) and 13, 277 patients were classified as severe grade (corticosteroid group: 1, 338, non-corticosteroid group: 11, 939). The 90-day survival rate was higher in the non-corticosteroid group than in the corticosteroid group in patients with pneumonia of overall grade (weighted hazard ratio [HR]: 1.36; P  < 0.001) and those with mild-to-moderate grade (weighted HR: 1.46; P  < 0.001). However, there were no significant differences in the outcomes between the two groups in those with severe grade (weighted HR: 1.08; P  = 0.38). Conclusions: Additive systemic corticosteroid therapy may be related to poor 90-day prognosis in patients with mild-to-moderate grade community-onset pneumonia, although it may not be positively associated with its prognosis in those with severe grade.